The Great Debt Divergence and its Implications for the Covid-19 Crisis: Mapping Corporate Leverage as Power - Joseph Baines; Sandy Brian Hager (City, University of London, City Political Economy Research Centre (CITYPERC), 2021)
The COVID-19 pandemic has amplified longstanding concerns about mounting levels of corporate debt in the United States. This article places the current conjuncture in its historical context, analysing corporate indebtedness against the backdrop of increasing corporate concentration. Theorising leverage as a form of power, we find that the leverage of large non-financial firms increased in recent decades, while their debt servicing burdens decreased. At the same time, smaller firms experienced sharp deleveraging alongside increasing debt servicing costs. Crucially, smaller corporations also registered severe losses over this period, while large corporations remained profitable, and in fact doubled their net profit margins from the early-1990s to the present. Taken together, the results from our mapping exercise uncover a series of dramatic changes in the financial fortunes of large versus smaller firms in recent decades, a phenomenon we refer to as the great debt divergence. We explain this divergence with reference to the dynamics of power in the era of 'shareholder capitalism,' and we argue that the US political economy in the post-COVID 19 world is likely to resemble the preCOVID 19 one, only with more market turmoil, more concentration, more inequality, and even less investment.
Keywords: 330